2017
DOI: 10.1002/ece3.3665
|View full text |Cite
|
Sign up to set email alerts
|

Drivers of apoplastic freezing in gymnosperm and angiosperm branches

Abstract: It is not well understood what determines the degree of supercooling of apoplastic sap in trees, although it determines the number and duration of annual freeze–thaw cycles in a given environment. We studied the linkage between apoplastic ice nucleation temperature, tree water status, and conduit size. We used branches of 10 gymnosperms and 16 angiosperms collected from an arboretum in Helsinki (Finland) in winter and spring. Branches with lower relative water content froze at lower temperatures, and branch wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 81 publications
(171 reference statements)
1
20
0
Order By: Relevance
“…In late winter, branch-and trunk-soluble sugars of Pinus koraiensis positively correlated with PLC and were overall more abundant than in summer [49]. This indicates that sugars mobilization over winter might represent a cold hardening strategy [48], but could be also putatively related to the need of maintaining and/or restoring hydraulic function [50,51] (see below).…”
Section: Stem Nscs Dynamics and The Maintenance Of Hydraulic Functionmentioning
confidence: 95%
“…In late winter, branch-and trunk-soluble sugars of Pinus koraiensis positively correlated with PLC and were overall more abundant than in summer [49]. This indicates that sugars mobilization over winter might represent a cold hardening strategy [48], but could be also putatively related to the need of maintaining and/or restoring hydraulic function [50,51] (see below).…”
Section: Stem Nscs Dynamics and The Maintenance Of Hydraulic Functionmentioning
confidence: 95%
“…Based on the presented study, several knowledge gaps with respect to winter embolism can be identified: first, the process of ice formation in plant xylem and how it leads to embolism is still not sufficiently understood (e.g. Lintunen et al , , ; Charrier et al , ). Considering the relevance of high altitude and latitude forest ecosystems, substantial knowledge of the eco‐physiological limits of trees is important, and information on freezing‐related mechanisms a prerequisite.…”
Section: Conclusion and Remaining Knowledge Gapsmentioning
confidence: 99%
“…1) at the sample base. Freezing was induced when the xylem temperature at the stem base (outside the cuvette) was around −1.5°C in the saturated samples and around -3.0°C in the dehydrated samples to mimic their natural freezing temperatures (Lintunen et al 2018). In experiment 3, artificial freezing was induced at the stem base at −1.5°C in the first two cycles, while freezing occurred spontaneously in the third cycle (due to the dehydrated surface of the debarked section, induction of freezing was not possible).…”
Section: Freezing Experimentsmentioning
confidence: 99%